2001
DOI: 10.1002/1096-8628(20010722)102:1<11::aid-ajmg1413>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations in a cohort of 41 Rothmund-Thomson syndrome patients

Abstract: Rothmund-Thomson syndrome (RTS) is a rare autosomal recessive genodermatosis characterized by a poikilodermatous rash starting in infancy, small stature, skeletal abnormalities, juvenile cataracts, and predisposition to specific cancers. We have identified a contemporary cohort of 41 patients to better define the clinical profile, diagnostic criteria, and management of patients with RTS. Patients with the diagnosis of RTS were ascertained by referrals from dermatology, ophthalmology, genetics, and oncology or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
228
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(244 citation statements)
references
References 32 publications
4
228
0
2
Order By: Relevance
“…4 To date, no malignancies have developed in the elder sibling, despite the fact that RTS is a syndrome predisposing to cancer, particularly osteosarcoma, that has an estimated prevalence of 30% and a mean age at diagnosis of 11 years. 16 Interestingly, from literature revision we noticed that 10 reported patients (9 RTS and 1 RAPADILINO) carry the c.2269C4T mutation (p.Q757*), 1,2,17,18 mapping 3 nt upstream the here described c.2272C4T mutation. No transcript analysis has been performed for the c.2269C4T, but according to our ESEFinder analysis (data not shown), this mutation is also predicted to be a splicing instead of a truncating mutation.…”
Section: Growth Parametersmentioning
confidence: 64%
“…4 To date, no malignancies have developed in the elder sibling, despite the fact that RTS is a syndrome predisposing to cancer, particularly osteosarcoma, that has an estimated prevalence of 30% and a mean age at diagnosis of 11 years. 16 Interestingly, from literature revision we noticed that 10 reported patients (9 RTS and 1 RAPADILINO) carry the c.2269C4T mutation (p.Q757*), 1,2,17,18 mapping 3 nt upstream the here described c.2272C4T mutation. No transcript analysis has been performed for the c.2269C4T, but according to our ESEFinder analysis (data not shown), this mutation is also predicted to be a splicing instead of a truncating mutation.…”
Section: Growth Parametersmentioning
confidence: 64%
“…Various manifestations reported include: 4,5 • Head, ENT, eye: microcephaly, juvenile cataracts, corneal dystrophy, saddle nose;…”
Section: Discussionmentioning
confidence: 99%
“…Molecular testing allows for the correct diagnosis, which is necessary for accurate targeting of syndrome-specific oncosurveillance. 12 A study on the response to therapy for osteosarcoma in patients with RTS indicated that these patients do not present the same level of sensitivity to genotoxic agents as patients with other chromosomal instability disorders. Therefore, they should be treated initially with conventional doses.…”
Section: Clinical Specificity (Proportion Of Negative Tests If the DImentioning
confidence: 99%